Faktor yang Mempengaruhi Kejadian Dermatitis Kontak Akibat Kerja pada Pengrajin Tahu di Keluarahan Gunung Sulah - Justiani, Andinni Aurellia; Kurniawaty, Evi; Rahmayani, Fidha; Anggraini, Dwi Indria (Jurnal Dunia Kesmas, 2024)
Occupational health and safety risks can arise in workers, the most common is contact dermatitis. Occupational Contact Dermatitis (OCD) is an inflammatory response of the skin that can be acute or chronic due to exposure with irritants or allergens at work. Tofu craftsmen are always exposed to tofu coagulation substances and water that can induce skin irritation reactions. Therefore, this study aims to determine the factors that influence the incidence of OCD in tofu craftsmen in Gunung Sulah Village, Way Halim District, Bandar Lampung. This research is analytical observational study with cross sectional. The sample of this research was 65 tofu craftsmen who were selected by the total sampling method. Data was collected by filling out questionnaires and diagnosed by a doctor. The data was analyzed by univariate and bivariate. The result was 56,9% has contact dermatitis. There is significant association between OCD with the exposure of personal protective equipment (p-value = 0,001), personal hygiene (p-value = 0,015), work periode (p-value = 0,043), and length of contact (p-value = 0,028). There is a significant association between personal protective equipment, personal hygiene, work periode, and length of contact with the incidence contact dermatitis in tofu craftsmen in Gunung Sulah Village.